Syariah Capital Market Instruments: Structures, Compliance, and Market Relevance - Karamillah, Abdussalam (Islamicate Institute, 2019)
This study investigates the instruments available in the Syariah capital market, focusing on their structural foundations, compliance with Islamic legal principles, and market relevance. Using a qualitative, document-based approach, the research examines core instruments including sukuk, Syariah-compliant stocks, Islamic mutual funds, and Islamic real estate investment trusts (i-REITs). These instruments are structured to comply with Syariah prohibitions on riba, gharar, and maysir, and support risk-sharing and ethical investment. Findings reveal that these tools play a critical role in broadening financial inclusion, aligning investment with Islamic ethics, and supporting economic development. The study also identifies key regulatory and technological challenges while highlighting opportunities for standardization and global integration. By synthesizing theoretical, legal, and institutional dimensions, this research offers new insights into the future direction of Islamic financial instruments and their potential to serve both faith-based and ethical investors worldwide.